Cardiac motion and spillover correction for quantitative PET imaging using dynamic MRI. Issue 2 (15th January 2019) - Marchesseau, Stephanie; Totman, John J.; Fadil, Hakim; Leek, Francesca A. A.; Chaal, Jasper; Richards, Mark; Chan, Mark; Reilhac, Anthonin
Abstract : Purpose: Cardiac positron emission tomography/magnetic resonance imaging (PET/MRI) acquisition presents novel clinical applications thanks to the combination of viability and metabolic imaging (PET) and functional and structural imaging (MRI). However, the resolution of PET, as well as cardiac and respiratory motion in nongated cardiac imaging acquisition protocols, leads to a reduction in image quality and severe quantitative bias. Respiratory or cardiac motion is customarily addressed with gated reconstruction which results in higher noise. Methods: Inspired by a method that has been used in brain PET, a practical correction approach, designed to overcome these existing limitations for quantitative PET imaging, was developed and applied in the context of cardiac PET/MRI. The correction approach for PET data consists of computing the mean density map of each underlying moving region, as obtained with MRI, and translating them to the PET space taking into account the PET spatial and temporal resolution. Using these tissue density maps, the method then constructs a system of linear equations that models the activity recovery and cross‐contamination coefficients, which can be solved for the true activity values. Physical and numerical cardiac phantoms were employed in order to quantify the proposed correction. The full correction pipeline was then used to assess differences in metabolic function between scar and healthy myocardium in eight patients with recent acute myocardial infarction using [ 11 C]‐acetate. Data from ten additional patients, injected with [ 18 F]‐FDG, were used to compare the method to the standard electrocardiography (ECG)‐gated approach. Results: The proposed method resulted in better recovery (from 32% to 95% on the simulated phantom model) and less residual activity than the standard approach. Higher signal‐to‐noise and contrast‐to‐noise ratios than ECG‐gating were also witnessed (Signal‐to‐noise ratio (SNR) increased from 2.92 to 5.24, contrast‐to‐noise ratio (CNR) increased from 62.9 to 145.9 when compared to a four‐gate reconstruction). Finally, the relevance of this correction using [ 11 C]‐acetate PET patient data, for which erroneous physiological conclusions could have been made based on the uncorrected data, was established as the correction led to the expected clinical results. Conclusions: An efficient and simple method to correct for the quantitative biases in PET measurements caused by cardiac motion has been developed. Validation experiments using phantom and patient data showed improved accuracy and reliability with this approach when compared to simpler strategies such as gated acquisition or optimal regions of interest (ROI). Abstract :